IKLAN LAYANAN MASYARAKAT TENTANG DAMPAK SAMPAH ANORGANIK TERHADAP LINGKUNGAN MELALUI MEDIA POSTER - Riri Trinanda, S.Pd., M.Sn., Trisno Susanto, Drs. Nasrul Kamal, M.Sn., (Serupa The Journal of Art Education, 2016)
Inorganic rubbish has the very afraidly effect, the charaters inorganic rubbish is very difficult to unravel at tens until hundreds of years. For that we need to invite people to not throw rubbish at random, especially in this case the writer approach the people with public service announ cemants about inoganic rubbish impact to the environment cultivation of media public service with advertising turtle as a figure with the tagline â€œdo you knowâ€ with body copy â€œ100 thousand turtles and sea birds die each years because swallow plastic and twisted it. There are many ways to resuscitate one of them by giving information abaout the nagative effects of inorganic rubbish through public service announcements.Keyword : Inorganic rubbish ,turtle ,posters ,public service announcements